Solenoid fringe field effects for the neutrino factory Linac - Mad-X investigation - Aslaninejad,M; Bontoiu,C; Pasternak,J; Pozimski,J; Bogacz,A (Ipac 2010 1st International Particle Accelerator Conference, 2010)
International Design Study for the Neutrino Factory (IDS-NF) assumes the first stage of muon acceleration (up to 900 MeV) to be implemented with a solenoid based Linac. The Linac consists of three styles of cryo-modules, containing focusing solenoids and varying number of SRF cavities for acceleration. Fringe fields of the solenoids and the focusing effects in the SRF cavities have significant impact on the transverse beam dynamics. Using an analytical formula, the effects of fringe fields are studied in MAD-X. The resulting betatron functions are compared with the results of beam dynamics simulations using OptiM code.